Finite element study of the biomechanical effects on the rotator cuff under load - Yang, Zhengzhong; Xu, Guangming; Yang, Jiyong; Lin, Xiaosheng (Frontiers in Bioengineering and Biotechnology, 2023)
Rotator cuff injuries account for 50% of shoulder disorders that can cause shoulder pain and reduced mobility. The occurrence of rotator cuff injury is related to the variation of shoulder load, but the mechanical changes in shoulder tissue caused by load remain unclear. Therefore, the mechanical results of the rotator cuff tissue during glenohumeral abduction and adduction were analyzed based on a finite element shoulder model with non-load and 7.5 kg load. The results showed that the maximum von Mises stress on the supraspinatus muscle was larger than the subscapularis, infraspinatus, and teres minor muscles during glenohumeral abduction, respectively. Compared with the non-load group, the maximum von Mises stress of the supraspinatus muscle increased by 75% in the load group at 30° abduction. In the load group, the supraspinatus joint side exhibited an average stress that was 32% greater than that observed on the bursal side. The von Mises stress on the infraspinatus muscle was higher than in other rotator cuff tissues during adduction. The infraspinatus muscle increased by 36% in the load group compared to the non-load group at 30° adduction. In summary, the increased load changed the mechanical distribution of rotator cuff tissue and increased the stress differential between the joint aspect and the bursal aspect of the supraspinatus tendon.